Government Health Insurance Schemes and Their Benefits to The Indian Population: An Overview - Uma Phalswal; Neeraja VK; Priyanhi Dixit; Ashok Kumar Bishnoi (Medsci Publications, 2023)
In today's scenario accelerating cost of health significantly impact the health of people and the populace creating a monetary burden on poor households. One of the key concerns while tackling healthcare disparities is out-of-pocket expenses (OOPE). Providing financial safety and provide universal coverage to the entire populace are the main goal of health schemes. Health policies in India are based on equity prioritising the needs of the poor and underprivileged. Likewise, there is a discrepancy in the consistency of information and knowledge regarding the scheme among the beneficiaries. A review was created to help medical and nursing professionals to gain comprehensive knowledge of various health schemes. We tried to give an overview of various health schemes including Ayushman Bharat Yojana, Aam Aadmi Bima Yojana (AABY), Pradhan Mantri Suraksha Bima Yojana (PMSBY), Rashtriya Swasthya BimaYojana (RSBY), Central Government Health Scheme (CGHS), Employees State Insurance Scheme (ESIC), Employee Health Scheme and various state-level health schemes.  include, Yeshasvini Health Insurance Scheme, Mahatma Jyotiba Phule Jan Arogya Yojana, Chief Minister Comprehensive Health Insurance Scheme, Mukhyamantri Amrutum Yojana, Karunya Health Scheme, Awaz Health Insurance Scheme, Telangana State Govt Employees and Journalist Health Scheme, Dr Ysr Aarogyastri Health Care Trust, Mukhyamantri Chiranjeevi Yojana, Rajasthan Government Health Scheme (RGHS), and Aarogya Raksha.